The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1242/dmm.043638
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Duchenne muscular dystrophy: myonecrosis, inflammation and oxidative stress

Abstract: Duchenne muscular dystrophy (DMD) is a lethal, X-linked disease that causes severe loss of muscle mass and function in young children. Promising therapies for DMD are being developed, but the long lead times required when using clinical outcome measures are hindering progress. This progress would be facilitated by robust molecular biomarkers in biofluids, such as blood and urine, which could be used to monitor disease progression and severity, as well as to determine optimal drug dosing before a full clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 117 publications
0
68
0
2
Order By: Relevance
“…Serum creatine kinase levels reflect the degree of muscle fibre damage and are usually normal or only slightly raised in FSHD ( 1 ). By comparison, DMD generally exhibits high serum creatine kinase levels with severe pathology in many muscles ( 54 ). This is accompanied by a robust regenerative response initially in DMD: for example, the proportion of regenerating fibres expressing developmental MyHC isoforms varied from 38 to 47% in quadriceps biopsies from four DMD patients aged 4–13 years ( 55 ), 24–33% in muscle biopsies from five DMD patients aged 4.3–8.2 years ( 20 ) and a mean of 32% in muscle biopsies from three DMD patients aged 3.3–6.8 years ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatine kinase levels reflect the degree of muscle fibre damage and are usually normal or only slightly raised in FSHD ( 1 ). By comparison, DMD generally exhibits high serum creatine kinase levels with severe pathology in many muscles ( 54 ). This is accompanied by a robust regenerative response initially in DMD: for example, the proportion of regenerating fibres expressing developmental MyHC isoforms varied from 38 to 47% in quadriceps biopsies from four DMD patients aged 4–13 years ( 55 ), 24–33% in muscle biopsies from five DMD patients aged 4.3–8.2 years ( 20 ) and a mean of 32% in muscle biopsies from three DMD patients aged 3.3–6.8 years ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in chronic liver and kidney diseases, as well as in diabetes mellitus, the percentage of cysteinylated albumin (Cys34-S-S-Cys) is markedly increased [ 116 ]. In recent years, it has been shown that oxidised albumin can be a biomarker of the severity of such diseases as hyperparathyroidism [ 152 ], acute ischemic stroke [ 153 ], Parkinson’s disease [ 154 ], Alzheimer’s disease [ 155 ], Duchenne muscular dystrophy [ 156 ], etc.…”
Section: Antioxidant Properties Of Albumin: Practical Applicationmentioning
confidence: 99%
“…Primary abnormalities in caveolin-3 are associated with certain forms of muscular dystrophy and the altered expression of this protein is postulated to also play a pathophysiological role in dystrophinopathy [ 39 ]. Importantly, new findings on the underlying mechanisms of dystrophic alterations are crucial for the identification of robust and disease-specific biomarker molecules [ 40 , 41 , 42 , 43 ] and the development of novel diagnostic approaches [ 44 ], as well as the design of innovative therapies to restore the dystrophin complex and counteract secondary aspects involved in progressive muscle wasting [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%